Formulas for the computation of the Tutte polynomial of graphs with parallel classes - Eunice Mphako-Banda; Julian A. Allagan (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2018)
We give some reduction formulas for computing the Tutte polynomial of any graph with parallel classes. Several examples are given to illustrate our results.